2014
DOI: 10.3390/toxins6030850
|View full text |Cite
|
Sign up to set email alerts
|

Elapid Snake Venom Analyses Show the Specificity of the Peptide Composition at the Level of Genera Naja and Notechis

Abstract: Elapid snake venom is a highly valuable, but till now mainly unexplored, source of pharmacologically important peptides. We analyzed the peptide fractions with molecular masses up to 10 kDa of two elapid snake venoms—that of the African cobra, N. m. mossambica (genus Naja), and the Peninsula tiger snake, N. scutatus, from Kangaroo Island (genus Notechis). A combination of chromatographic methods was used to isolate the peptides, which were characterized by combining complimentary mass spectrometric techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
4
15
0
4
Order By: Relevance
“…Of note, hemotoxic effects are rarely observed in envenomation by Asiatic elapids due to the absence of procoagulant and hemorrhagic enzymes in their venoms [27]. On the other hand, the identification of Kunitz-type serine protease inhibitors (~7%, KSPI) in this study is in agreement with previous findings of KSPI from transcription activity in the venom-gland [28] and protein isolation from the venom [29] of Australian tiger snake. The role of KSPI in N. scutatus envenomation is unclear but potentially related to the facilitation of presynaptic neurotoxicity through ion channel inhibition and chaperoning the neurotoxic PLA 2 s [30,31].…”
Section: Proteome Of Notechis Scutatus Venomsupporting
confidence: 93%
See 2 more Smart Citations
“…Of note, hemotoxic effects are rarely observed in envenomation by Asiatic elapids due to the absence of procoagulant and hemorrhagic enzymes in their venoms [27]. On the other hand, the identification of Kunitz-type serine protease inhibitors (~7%, KSPI) in this study is in agreement with previous findings of KSPI from transcription activity in the venom-gland [28] and protein isolation from the venom [29] of Australian tiger snake. The role of KSPI in N. scutatus envenomation is unclear but potentially related to the facilitation of presynaptic neurotoxicity through ion channel inhibition and chaperoning the neurotoxic PLA 2 s [30,31].…”
Section: Proteome Of Notechis Scutatus Venomsupporting
confidence: 93%
“…The occurrence of natriuretic peptide in this study (~2%) is also supported by the previous report on natriuretic peptide isolated from the venom [29]. This toxin may serve to induce hypotension, an effect that is probably important to aid in prey immobilization for the snake [29,32]. Other toxins detected at low abundance (b 2%) in this study were expressed proteins previously identified only at the level of transcription (L-amino acid oxidase, nerve growth factor, cysteine-rich secretory protein, vespryn), or have never been reported previously (acetylcholinesterase, 5′-nucleotidase, phospholipase B) for this species.…”
Section: Proteome Of Notechis Scutatus Venomsupporting
confidence: 93%
See 1 more Smart Citation
“…After the discovery of these first BPPs, similar proline-rich peptides were isolated from different snake venoms [3134] and even frogs skin secretion [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…Even with this accumulated history of success, new features are being discovered for BPPs in many different Viperidae venoms (e.g. Gomes et al, 2007;Rioli et al, 2008) and, even in Elapidae venom such as Naja mossambica (Munawar et al, 2014). Usually, BPP precursors are composed by BPPs, BIP and CNP, separated by propeptides that are cleaved into the active peptides.…”
Section: Crotaminementioning
confidence: 97%